Enhancing PLP-Binding Capacity of Class-III ω-Transaminase by Single Residue Substitution - Roura Padrosa, David; Alaux, Raphael; Smith, Phillip; Dreveny, Ingrid; López-Gallego, Fernando; Paradisi, Francesca (Frontiers in Bioengineering and Biotechnology, 2019)
Transaminases are pyridoxal-5’-phosphate (PLP) binding enzymes, broadly studied for their potential industrial application. Their affinity for PLP has been related to their performance and operational stability and while significant differences in PLP requirements have been reported, the landscape of the PLP-binding pocket is highly conserved. In this study, thorough analysis of the residue interaction network of three homologous transaminases Halomonas elongata (HeTA), Chromobacterium violaceum (CvTA) and Pseudomonas fluorescens (PfTA) that HeTA revealed a single residue difference in their PLP binding pocket: an asparagine at position 120 in HeTA. N120 is suitably positioned to interact with an aspartic acid known to protonate the PLP pyridinium nitrogen, while the equivalent position is occupied by a valine in the other two enzymes. Three different mutants were constructed (HeTA-N120V, CvTA-V124N and PfTA-V129N) and functionally analyzed. Notably, in HeTA and CvTA, the asparagine variants, consistently exhibited a higher thermal stability and a significant decrease in the dissociation constant (Kd) for PLP, confirming the important role of N120 in PLP binding. Moreover, the reaction intermediate pyridoxamine-5’-phosphate (PMP) was released more slowly into the bulk, indicating that the mutation also enhances their PMP binding capacity. The crystal structure of PfTA, elucidated in this work, revealed a tetrameric arrangement with the PLP binding sites near the subunit interface. In this case, the V129N mutation had a negligible effect in PLP-binding, but it destabilized the quaternary structure which reduces its temperature stability.